Financial Performance Analysis of Islamic Bank Using FDR, ROA, ROE, and NPF Ratios - Syafaat, Fitra; Timuriana, Tiara (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
This study examines the long-term financial performance of Bank Victoria Syariah, a sharia banking institution in Indonesia, by analyzing four key financial ratios: Financing to Deposit Ratio (FDR), Return on Assets (ROA), Return on Equity (ROE), and Non-Performing Financing (NPF) from 2014 to 2023. Addressing the gap in the existing literature that often lacks in-depth institution-specific analysis, this study applies a quantitative descriptive method using audited financial statements to track trends in financial intermediation, profitability, and credit risk management within a Sharia-compliant framework. The findings show that although the bank initially faced challenges such as negative profitability and high credit risk, significant improvements were achieved in recent years—especially post-2021—as evidenced by a decrease in the NPF rate and an increase in ROA and ROE. These results suggest that strategic financial management and effective risk mitigation efforts play a significant role in improving bank performance and resilience. This study contributes meaningful insights for practitioners, regulators, and academics who seek to strengthen institutional performance, improve risk governance, and ensure long-term sustainability in the Islamic banking sector through more targeted financial strategies based on Sharia principles.